Constructing hollow graphene nano-spheres confined in porous amorphous carbon particles for achieving full X band microwave absorption. (February 2019) - Xu, Hailong; Yin, Xiaowei; Zhu, Meng; Li, Minghang; Zhang, Heng; Wei, Hanjun; Zhang, Litong; Cheng, Laifei
Abstract: The development of high-performance carbonaceous microwave absorbers to achieve full X band (8.2–12.4 GHz) efficient microwave absorption with lower filler loading ratio is highly desirable but remains challenging. Here, a kind of hollow graphene nano-spheres uniformly confined in porous amorphous carbon particles (HGS@PAC) are fabricated via a facile pyrolysis of bi-metal organic framework (bi-MOF). The successful construction of hollow graphene nano-spheres (HGS) by the in situ catalysis of Co in the framework of bi-MOF significantly improve the interface polarization and conductive loss of HGS@PAC, which ensures the high enough absorption intensity with lower filler loading ratio when used as microwave absorbers. The optimal HGS@PAC demonstrate excellent microwave absorption performance, achieving an effective absorption bandwidth of 4.2 GHz which covers the whole X band with 10 wt.% loading content and the minimum reflection coefficient reaches −32.43 dB at 9.19 GHz. In addition, compared with other MOF derived absorbers (such as Co/C, C/TiO2 and CNTs/Co), the HGS@PAC exhibit broader effective absorption bandwidth and stronger absorption intensity. Therefore, this work provides a promising method for the design and synthesis of HGS uniformly confined in PAC with high-performance microwave absorption. Graphical abstract: Hollow graphene nano-spheres with dozen nanometer in size confined in porous amorphous carbon matrix, which possess enhanced interface polarization and conductive loss from highly graphitization HGS and well impedance match from the amorphous state of bulk porous carbon, exhibit excellent microwave absorption performance with an RCmin lower to −32.43 dB and effective absorption bandwidth covers the whole X band with a filler loading of only 10 wt.%. Image 1